2018
DOI: 10.1101/331777
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estrogen Regulates the Satellite Cell Compartment in Females

Abstract: Skeletal muscle mass, strength, and regenerative capacity decline with age, with many measures showing greater deterioration in females about the time estrogen levels decrease at menopause. Here we show that maintenance of muscle stem cells, satellite cells, as well as selfrenewal and differentiation into muscle fibers, are severely compromised by estrogen deficiency.Mechanistically, by hormone replacement, use of a selective estrogen-receptor modulator (bazedoxifene), and conditional estrogen receptor knockou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 84 publications
1
59
0
Order By: Relevance
“…Our results also indicate that Cre-induced cytoplasmic-localized fluorescent reporters should be used with caution for accurately determining the contribution of satellite cell fusion to muscle fibers. 29–32 , 126 Future experiments involving satellite cell-specific inhibition of EV release, as well as genetic manipulation of specific miRNAs in satellite cells in vivo will help provide more detailed insight into satellite cell regulation of muscle fiber gene expression by fusion-independent mechanisms. Satellite cells coordinate adaptation to support maximal long-term muscle hypertrophy, 19 which may in part be due to EV delivery of miRNA to muscle fibers that affect ECM-related gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also indicate that Cre-induced cytoplasmic-localized fluorescent reporters should be used with caution for accurately determining the contribution of satellite cell fusion to muscle fibers. 29–32 , 126 Future experiments involving satellite cell-specific inhibition of EV release, as well as genetic manipulation of specific miRNAs in satellite cells in vivo will help provide more detailed insight into satellite cell regulation of muscle fiber gene expression by fusion-independent mechanisms. Satellite cells coordinate adaptation to support maximal long-term muscle hypertrophy, 19 which may in part be due to EV delivery of miRNA to muscle fibers that affect ECM-related gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this theory, muscles from Ovx mice have been shown to be weaker following various injuries (e.g. freeze injury, eccentric contraction‐induced injury) compared to control or Ovx+E 2 mice (Collins et al., 2019; Kosir et al., 2015; Le et al., 2018; Schneider, Fine, Nadolski, & Tiidus, 2004). Oestradiol may influence recovery of strength by regulating various pathways of skeletal muscle degeneration and regeneration.…”
Section: Introductionmentioning
confidence: 98%
“…Loss of muscle strength in females due to E 2 deficiency is attributed to inadequate preservation of skeletal muscle mass (Kamanga‐Sollo, Thornton, White, & Dayton, 2017) and reduced quality of the remaining skeletal muscle (Lai, Collins, Colson, Kararigas, & Lowe, 2016; Moran et al., 2007; Qaisar et al., 2013). Although E 2 likely works through various mechanisms, leading candidates contributing to strength loss are apoptotic‐induced reductions in muscle mass (Collins et al., 2019; La Colla, Vasconsuelo, Milanesi, & Pronsato, 2017; Laakkonen et al., 2017), modifications to myosin heavy chain function (Moran et al., 2007; Qaisar et al., 2013) through phosphorylation of the regulatory light chain (Collins et al., 2018; Lai et al., 2016), abnormal inflammation (Tiidus et al., 2001) and impaired mitochondrial function (Ribas et al., 2016; Valencia et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both are nuclear transcriptional factors involved in various cellular functions, with common and different roles, and distinct effects ( Hamilton et al., 2017 ). Recent studies demonstrated that ERα is involved in mitochondrial integrity ( Ribas et al., 2016 ), lipid metabolism ( Schweisgut et al., 2017 ), atrophy ( Ogawa et al., 2015 ), and regeneration ( Collins et al., 2019 ) in skeletal muscle. Although E2 preferably binds to ERα, we have found that consecutive intake of soymilk containing isoflavones, which preferentially bind to ERβ, ameliorated muscle atrophy and satellite cell dysfunction in ovariectomized female mice ( Kitajima et al., 2017 ; Kitajima and Ono, 2016 ), suggesting that ERβ signaling is also a factor that regulates both skeletal muscles and satellite cells.…”
Section: Introductionmentioning
confidence: 99%